2020
DOI: 10.3390/su12072974
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Local Climate Zones Using ArcGIS-Based Method and Exploring Land Surface Temperature Characteristics in Chenzhou, China

Abstract: The local climate zone (LCZ) has become a new tool for urban heat island research. Taking Chenzhou as the research object, eight urban spatial form elements and land cover elements are calculated respectively through ArcGIS, Skyhelios and ENVI software. The calculation results are then rasterized and clustered in ArcGIS to obtain the LCZ map at a resolution of 200 m. Afterwards, the land surface temperature (LST) of different local climate zones in the four seasons from 2017 to 2018 is further analyzed using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Many studies compared different machine learning algorithms for LCZ classification, and it can be concluded that their performance varies from city to city (Bechtel et al, 2016;Bechtel & Daneke, 2012;La et al, 2020;Mushore et al, 2019;Xu et al, 2017bXu et al, , 2018 Multi-source remote sensing and GIS data have been used for calculating LCZ parameters. For surface structure parameters, the sky view factor (SVF) can be calculated using digital surface model (DSM) (Bartesaghi Koc et al, 2017;Mitraka et al, 2015;Quan, 2019;Zhao et al, 2019a;Zheng et al, 2018), building data (Chen et al, 2020b;Nassar et al, 2016), and Google Street View (Middel et al, 2018). The aspect ratio can be calculated as the mean building height divided by the mean street width using building data (Chen et al, 2020b;Zheng et al, 2018), and as the maximum height divided by average width of ground surface based on the normalized DSM (Zhao et al, 2019a).…”
Section: Classification Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies compared different machine learning algorithms for LCZ classification, and it can be concluded that their performance varies from city to city (Bechtel et al, 2016;Bechtel & Daneke, 2012;La et al, 2020;Mushore et al, 2019;Xu et al, 2017bXu et al, , 2018 Multi-source remote sensing and GIS data have been used for calculating LCZ parameters. For surface structure parameters, the sky view factor (SVF) can be calculated using digital surface model (DSM) (Bartesaghi Koc et al, 2017;Mitraka et al, 2015;Quan, 2019;Zhao et al, 2019a;Zheng et al, 2018), building data (Chen et al, 2020b;Nassar et al, 2016), and Google Street View (Middel et al, 2018). The aspect ratio can be calculated as the mean building height divided by the mean street width using building data (Chen et al, 2020b;Zheng et al, 2018), and as the maximum height divided by average width of ground surface based on the normalized DSM (Zhao et al, 2019a).…”
Section: Classification Algorithmsmentioning
confidence: 99%
“…For surface structure parameters, the sky view factor (SVF) can be calculated using digital surface model (DSM) (Bartesaghi Koc et al, 2017;Mitraka et al, 2015;Quan, 2019;Zhao et al, 2019a;Zheng et al, 2018), building data (Chen et al, 2020b;Nassar et al, 2016), and Google Street View (Middel et al, 2018). The aspect ratio can be calculated as the mean building height divided by the mean street width using building data (Chen et al, 2020b;Zheng et al, 2018), and as the maximum height divided by average width of ground surface based on the normalized DSM (Zhao et al, 2019a). The height of roughness elements can be calculated as a mean height of buildings weighted by the building footprints using building data (Lelovics et al, 2014;Nassar et al, 2016;Quan, 2019;Zheng et al, 2018).…”
Section: Classification Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The regionalization of the precipitation statistics has numerous applications in various water resource management fields, such as agriculture practices, spatial and temporal rainfall patterns, hydrological analysis, extreme event forecasting [55] and watershed management. There are several methods available to delineate climate regions, for example, subjective and objective partitioning, geographical convenience and multivariate analysis [54,56,57]. The arbitrary and slightly misleading demarcation approach for a region, which is based on administrative boundaries and physical and geographical groupings, is referred to as the geographical convenience method.…”
Section: Climate Zoningmentioning
confidence: 99%